Pemberdayaan Kelompok Wanita Tani Melalui Inovasi Dan Teknologi Pengemasan Permen Jamu Di O Mangunharjo - Ira Primalasari; Vera Octalia; M Nejatullah Sidqi (JURNAL CEMERLANG: Pengabdian pada Masyarakat, 2025)
The training aimed to provide knowledge about innovative herbal medicine product, specifically herbal candy and ut’s packaging. The goal of this activity was to increase the economics independence of herbal medicine artisans. The implementation method used a participatory training approach, including training in herbal candy making and the application of modern packaging technology. The results showed a significant increase in the knowledge and skills of women’s farmer group members regarding candy production techniques and more attractive packaging. Furthermore, the packaging innovation extended the product’s shelf life and increased competiveness in both local and online markets.